Prevalence of risky behaviors and related factors among students of Dezful University of Medical Sciences in 2014 - Malihe sohrabivafa (Iranian Journal of Psychiatry, 2017)
Introduction: Adolescence is a period of evolution that there is the incidence probability of risky behaviors such as drug abuse, risky sexual behavior and compatibility problems. The goal of this study was to investigate the prevalence rate of risky behaviors among students of Dezful University of Medical Sciences in 2014.